Multimedia Vehicular Smartphone Docking with GPS Tracking - Feliks Wida Satyamarda; Novembri Priyadmaji Widi Nugroho; Banu Wirawan Yohanes (Techné : Jurnal Ilmiah Elektroteknika, 2021)
The Internet of Things (IoT) connecting many electronic devices via internet has been ubiquitous in the last decade. For instance, electric or hybrid cars and autonomous vehicles which are supported by many automotive and IT companies. IoT does not only provide internal monitoring service of the devices, but also the environmental situation. Meanwhile, smartphones are equipped with embedded built-in sensors, and also providing wireless communications. In consequence, vehicular telematics based on smartphone is growing rapidly. This paper proposes a vehicular smartphone docking prototype. It aims not only to provide an affordable alternative to Android Auto and CarPlay, but also to complement them, particularly in vision and security cases. The main issue is that the driver should not be distracted while driving. Such distraction may cause road accident which can lead to severe injuries and even death. Therefore, it is important to design a vehicle smartphone docking to guarantee distraction avoidance and to provide multimedia and localization services. This vehicular smartphone docking architecture consists of an Android smartphone and a Raspberry Pi. Several test drives were conducted with perfect results. Based on the experiment results, this system is able to reduce the number of modules required within a smart vehicle.